ANALISIS STRATEGI METAKOGNITIF SISWA DALAM MEMAHAMI DAN MENYELESAIKAN SISTEM PERSAMAAN LINEAR DUA VARIABEL DITINJAU DARI PERBEDAAN GENDER - Ryan Nizar Zulfikar; Eva Dwika Masni (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2021)
The purpose of this study was to analyze students' metacognitive strategies in understanding and solving math problems in terms of gender differences. This type of research is based on a qualitative approach with a descriptive research design. Purposive sample technique is a technique of determining the subject based on certain criteria to make it easier to obtain the desired information. Data collection techniques in this study consisted of interviews, tests, documentation and observations. The data analysis technique in this study consists of reducing data, presenting data and making conclusions. For data validity, this study used triangulation. Triangulation is done by triangulation method. Method triangulation in this research uses two methods, namely interviews and documentation. Based on the results of data analysis, it shows that four aspects of metacognitive strategies, namely the awareness aspect, cognitive aspects, planning aspects and re-checking in understanding and solving mathematical problems in the material of the two-variable linear equation system show that the metacognitive strategies of female and male students in class X SMA 8 Kupang can be said to be good in accordance with the minimum completeness criteria set at school. Even though in the awareness and evaluation aspects, it was still seen that male and female students did not use metacognitive strategies, because understanding the concept in solving story problems was still not understood about the differences in collecting known data and being asked by mathematical modeling. Overall, male and female students were able to understand and solve problems using metacognitive strategies.